Quality of Living and Sustainability Indicators – City of Ljubljana, Vision 2050 - Sucic, Boris; Pusnik, Matevz; Cesen, Matjaz; Merse, Stane (Industrija, 2014)
The greatest challenge of future development of urban areas has been related with the sustainability issues. Unfortunately, sustainability issues and related costs of resources, including energy, occupy minds only of minority in the society. In the process of transition toward low carbon society many countries have set indicative targets which are revealing desired momentum of change but only at the national level. The absence of clear and direct transformation of national targets into implementation programmes at the local level was the crucial reason why many previous goals have not been achieved. Within the paper, six main sustainability indicators related to the quality of living in urban areas have been described and discussed. Indicators have been tested and customised during the analysis of future development challenges of the Slovenian capital, City of Ljubljana. Results of the analysis show that suggested indicators may be used in the process of municipal energy planning. During the research work, technology and sector oriented bottom up reference energy and environmental system model of City of Ljubljana has been developed. It is the first so complex reference energy and environmental system model that has been developed on the municipal level in the Southeast Europe.
Keywords: Urban development; Sustainable development; Urbanization; Energy; Quality of life